In silico deceased donor intervention research: A potential accelerant for progress. Issue 6 (28th February 2021) - Hobeika, Mark J.; Casarin, Stefano; Saharia, Ashish; Mobley, Constance; Yi, Stephanie; McMillan, Robert; Mark Ghobrial, Rafik; Osama Gaber, Ahmed
Abstract : Progress in deceased donor intervention research has been limited. Development of an in silico model of deceased donor physiology may elucidate potential therapeutic targets and provide an efficient mechanism for testing proposed deceased donor interventions. In this study, we report a preliminary in silico model of deceased kidney donor injury built, calibrated, and validated based on data from published animal and human studies. We demonstrate that the in silico model behaves like animal studies of brain death pathophysiology with respect to upstream markers of renal injury including hemodynamics, oxygenation, cytokines expression, and inflammation. Therapeutic hypothermia, a deceased donor intervention studied in human trials, is performed to demonstrate the model's ability to mimic an established clinical trial. Finally, future directions for developing this concept into a functional, clinically applicable model are discussed. Abstract : In silico models of neurologic death physiology may suggest new opportunities to advance deceased donor intervention research, as demonstrated by this exploratory study based on animal data.